Quantitative Anti-HBc in Liver Pathological States in Patients with Chronic Hepatitis B Virus Infection - Zhan-qing Zhang; Bi-sheng Shi; Wei Lu; Dan-ping Liu; Dan Huang; Yan-ling Feng (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Changes of hepatitis B core antigen antibody (anti-HBc) in liver pathological involvement in patients with chronic hepatitis B virus (HBV) infection have not been investigated in detail. This study aimed to explore evolving patterns of anti-HBc following liver pathological states and to investigate validities of anti-HBc for predicting liver pathological states. Methods. 254 HBeAg-positive and 237 HBeAg-negative patients with chronic HBV infection were enrolled. Liver pathological diagnoses referred to Scheuer standard, and anti-HBc was measured using chemiluminescence microparticle immunoassay. Results. Anti-HBc was significantly positively correlated with pathological grades and stages in both HBeAg-positive (rs = 0.312, P<0.0001, and rs = 0.268, P<0.0001) and HBeAg-negative (rs = 0.270, P<0.0001, and rs = 0.147, P=0.0237) patients. The medians of anti-HBc in pathological grades of G1, G2, and G3 and stages of S1, S2, S3, and S4 in HBeAg-positive patients were all significantly lower than those in HBeAg-negative patients (all P<0.005). The areas under receiver-operating characteristic curves (95% confidence interval) of anti-HBc for predicting pathological grades ≥G2 and ≥G3, and stages ≥S2 and =S4 in HBeAg-positive patients were 0.683 (0.622–0.740) and 0.662 (0.601–0.720), and 0.627 (0.564–0.687) and 0.683 (0.622–0.740), respectively, and in HBeAg-negative patients were 0.681 (0.618–0.740) and 0.702 (0.639–0.760), and 0.569 (0.503–0.633) and 0.630 (0.565–0.691), respectively. Conclusion. Following hepatic aggravation of necroinflammation and progression of fibrosis, anti-HBc increases gradually in HBeAg-positive patients and continues to increase gradually in HBeAg-negative patients, which is a useful but unsatisfactory marker for monitoring pathological states.